ORGANIZATION AND PRACTICAL EXPERIENCE OF ROSTOV CENTRE FOR MEDICAL PSYCHOLOGY (NEURO-CODING CENTRE) UNDER CURRENT CONDITIONS OF SOCIOLEGAL RELATIONS - Boris E. Olekhnovich; Sergey I. Sаmygin; Irina B. Olekhnovich; Boris B. Olekhnovich (Advanced Engineering Research, 2012)
The actual state of clinical psychology as a type of the business activity and a liberal science at the market of psychological and psychotherapeutic services in the Russian Federation is specified. The legal and socio-cultural obstacles for the clinical psychologist’s activity in Russia are analyzed. The effective mechanism for the integration of practitioners involved in the health care of the Russian citizens is offered.